Em conexão com a emoção : a importância do marketing emocional para criação de lovemarks - Novello, Luana (My University, 2020)
In a market scenario of intense competitiveness, the parity of products and services causes brands to seek new differentials. These differentials, which not only promote a good customer experience, but also contribute to a lasting relationship and mutual admiration between the parties. This highlights the role of emotions in the construction of what has been called the lovemark. Considering this context, this monographic work aims to analyze the relevance of emotional marketing strategies for building a lovemark. Based on this assumption, the following objectives were highlighted: analyzing the relevance of creating emotional marketing strategies for building a lovemark, identifying how emotion influences the consumer's choice decision and understanding which emotional marketing strategies are used to build a lovemark . For this, through review of the current bibliography, we sought to identify the role of the brand within this scenario of intense competitiveness, as well as the strategies for its management and the understanding of the concept of lovemark. Then, the transition from the traditional marketing proposal to the emotional marketing was contextualized, highlighting the great influence of emotions in the purchase decision process and in the relationship with consumers. The methodology used in this work was the case study of the Netflix platform, carried out through Netnography from its fanpage. Netflix has been identified as one of the most loved brands in Brazil and its humanized language and personified communication strategies have aroused the affection and involvement of its followers (sic).
Num cenário mercadológico de intensa competitividade, a paridade de produtos e serviços faz com que as marcas busquem novos diferenciais. Diferenciais estes, que não só promovam uma boa experiência ao cliente, mas que contribuam para uma relação duradoura e de mútua admiração entre as partes. Isso coloca em pauta o papel das emoções na construção daquilo que tem sido denominado como lovemark. Considerando o presente trabalho monográfico tem o objetivo de analisar a relevância de estratégias de marketing emocional para construção de uma lovemark. A partir deste pressuposto destacou-se como objetivos analisar a relevância da criação de estratégias de marketing emocional para construção de uma lovemark, identificar como a emoção influencia na decisão de escolha do consumidor e compreender quais estratégias de marketing emocional são usadas para construção de uma lovemark. Para isso, por meio da revisão da bibliografia vigente buscou-se identificar o papel da marca dentro deste cenário de intensa competitividade, bem como as estratégias para sua gestão e a compreensão do conceito de lovemark. Em seguida, contextualizou-se a transição da proposta do marketing tradicional para o marketing emocional, destacando a grande influência das emoções no processo de decisão de compra e de relacionamento com os consumidores. A metodologia utilizada neste trabalho foi o estudo de caso da plataforma Netflix, realizado através de Netnografia de sua fanpage. A Netflix tem sido apontada como uma das marcas mais amadas do Brasil e suas estratégias de linguagem humanizada e comunicação personificada tem despertado o afeto e envolvimento dos seus seguidores (sic).
Keywords: Publicidade; Marca de produtos; Marketing; Netflix (Firma)